Pemanfaatan Tongkol Jagung Dan Sekam Padi Menjadi Asap Cair Menggunakan Proses Pirolisis - Elssy, Elisabeth ; Abrina Anggraini, Sinar Perbawani; Yuniningsih, Susy (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Heat exchange causes cold water to change temperature where the cooling water temperature to rise because the resulting heat is carried by a fluid which is absorbed by the water. To overcome that we need some cooling to reduce the temperature of the water is by using a cooling tower. The goal is to find out and determine "the effect of adding a cooling tower to decrease the water temperature in the cooling bath steam distillation process of (Cymbopogon citratus) leaves ". Measure the temperature every 30 minutes after the distillate water dripping, and the process of repeated measurements simultaneously on a water bath cooler, condenser, cooling tower (cooling tower) and the distillate water. The process of measuring the temperature using a cooling tower with a water tank initial temperature was 270C with the old process for 3 hours. From this research can be concluded that: 1)At the time of the process without using an intermediary Cooling Tower For media water cooler during the 3 hour difference between 2-30C temperature rise to a maximum temperature ranging between 41-430C. 2) Cooling Tower Process using water as a cooling medium for 3 hours process, the maximum temperature ranges between 31-340C and the difference in temperature rise between 1-20C. 3)Comparison of the temperature of the process without the use of Cooling Tower and Cooling Tower using cooling water as its medium very different temperature difference is 34 : 430C with a temperature difference of 90C without using the Cooling Tower to use the Cooling Tower.